Repeat FNA Significantly Lowers Number of False Negative Results in Patients with Benign Nodular Thyroid Disease and Features of Chronic Thyroiditis - Dorota Słowińska-Klencka; Ewa Woźniak-Oseła; Bożena Popowicz; Stanisław Sporny; Mariusz Klencki (International Journal of Endocrinology)
Purpose. The aim of the study was to compare the risk of thyroid malignancy and efficacy of repeat FNA in patients with thyroid nodules diagnosed cytologically as benign lesion (BL) with features of chronic thyroiditis (BL-CT) and BL without CT features (BL-nCT). Methods. The analysis included 917 patients with BL-CT and 7046 with BL-nCT in the first FNA. Repeat biopsy was carried out in 787 patients of BL-CT and 5147 of BL-nCT; 218 patients of BL-CT and 2462 of BL-nCT were operated; in 88 cases of BL-CT and 563 of BL-nCT both ways of follow-up were available. Results. Outcome of repeat cytology implied surgery more frequently in patients with BL-CT than with BL-nCT—3.2% versus 1.9%, P < 0.05. Incidence of cancer (including incidentalomas) was higher in patients with BL-CT operated after one benign cytology than in patients with two benign FNA outcomes: 10.8% versus 1.6%, P < 0.05. In patients with BL-nCT that difference was not significant: 3.2% versus 2.6%. Conclusions. Patients with thyroid nodules diagnosed as BL with CT features have higher risk of malignancy than patients with BL without CT features. Repeat biopsy significantly lowers percentage of FN results in patients with BL-CT in the first FNA.